Editorial do CBIE 2025 - Pereira Júnior, Cleon Xavier; Pereira, Roberto; Pimentel, Edson; Nunes, Isabel; Maschio, Eleandro; Falcão, Taciana Pontual; Oliveira, Leander Cordeiro de; Seixas, Luma; Alves, Gabriel; Silva Junior, Deógenes; Dutra, Taynara; Amaral, Marília Abrahão; et al. (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE), 2025)
Este documento traz os elementos pré-textuais e comitês do CBIE 2025.